M. Kashgari outlook in the light of the texts of the Qur’an and the Hadith. (Journal of Oriental Studies, 2016)
This article discusses the outlook M. Kashgari. As well as examples of what M.Kashgari outlook is based on the Muslim worldview. This is proved by examples referring to the Koran and the Hadith, which are given in the works M. Kashgari. The final part describes M. Kashgari as a God-fearing man, stick to the pillars of Islam and faithfully served his country and Turkic languages. M. Kashgari given to the younger generation, as an example, is well aware of the tradition and history of his people.
Keywords: M. Kashgari; outlook; the Qur’an; the Hadith; the Turkish language